Site Visit and Needs Analysis for IoT and Solar Energy Integration in Greenhouse and Aquaponics Systems in Bojong Renged Village, Tangerang Regency - Fahmy Rinanda Saputri; Muhammad Salehuddin; Arief Iswariyadi; Satya Arisena Hendrawan; Vannessa Wong (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
This community service project aims to monitor the progress of implementing Internet of Things (IoT) and solar-powered agricultural systems in Bojong Renged Village, Tangerang Regency. A field visit was conducted on October 21, 2025, by a collaborative team from Universitas Multimedia Nusantara and Universitas Siber Indonesia following an initial Focus Group Discussion (FGD). The methods applied include field observations of greenhouse and aquaponics construction, interviews with farmer and fisheries groups, and environmental measurements such as temperature, humidity, water quality, and site conditions. The visit confirmed the installation of lightweight steel structures for the greenhouse and preliminary frameworks for aquaponics above fish ponds. Partners expressed the need for IoT-based temperature, pH, soil moisture, and water quality monitoring systems powered by solar energy. These findings provide practical implications for system design, including sensor selection, energy capacity planning, and community training modules. The results serve as a foundation for the next implementation phase toward a sustainable smart farming and aquaculture model.